SOSIALISASI DAN PENYULUHAN ANAK TUNARUNGU DI DESA AIR LATAK - Nora Fitria; Anisa Gustianah; Siwi Retno Palupi; Serly Noviani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to see an overview of the socialization of deaf children at home, school, and in the surrounding environment. This study uses a case study approach. A qualitative approach is used to obtain more complete and accurate data about the socialization of deaf children, which is very limited, and because of the limitations of the research subjects.The results of the study concluded that there were several assumptions about the deaf background of the respondents that could be identified, namely due to genetic factors, consuming too many drugs since childhood, or because of step. The impact of deafness is that the respondent is unable to use spoken language, the respondent is only able to use language cues in communicating with other people, the respondent's parents can accept the respondent's condition as it is, the respondent's parents remain optimistic so that. The respondent's friends regard the respondent as other normal friends, the difference is only the way of communicating with them, but there is no treatment of the respondent. The educators experienced difficulties in interacting with the respondents. The educators experienced difficulties in providing an assessment of the respondents' achievements.